2008
DOI: 10.1063/1.2904698
|View full text |Cite
|
Sign up to set email alerts
|

Near-field scanning optical microscopy with monolithic silicon light emitting diode on probe tip

Abstract: We describe optical and topographic imaging using a light emitting diode monolithically integrated on a silicon probe tip for near-field scanning optical microscopy (NSOM). The light emission resulted from a silicon dioxide layer buried between a phosphorus-doped N+ silicon layer and a gallium-doped P+ silicon region locally created at the tip by a focused ion beam. The tip was employed in a standard NSOM excitation setup. The probe successfully measured optical as well as topographic images of a chromium test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…With type-(1) and type-(2) probes, the light emission may not happen exactly at the physical tip of the scanning probe as indicated in Figure 1. We observed significant image shift between obtained topographic and optical images [4]. Because the type-(3) LED utilizes the probe tip as one of the electrodes, the location of the light source corresponds to the tip of the silicon probe.…”
Section: Imaging Experimentsmentioning
confidence: 96%
See 1 more Smart Citation
“…With type-(1) and type-(2) probes, the light emission may not happen exactly at the physical tip of the scanning probe as indicated in Figure 1. We observed significant image shift between obtained topographic and optical images [4]. Because the type-(3) LED utilizes the probe tip as one of the electrodes, the location of the light source corresponds to the tip of the silicon probe.…”
Section: Imaging Experimentsmentioning
confidence: 96%
“…This milling process induces re-deposition of gallium doped p-type silicon, which eventually creates a P-N junction [2] with a thin silicon dioxide layer as the light emitter [3]. The LED was typically driven at 4-8V and emitted light centered at 560nm [4]. (2) Electrostatic trapping of semiconductor nanoparticles Additional semiconductor nanoparticles at probe tip were used as the light source [5].…”
Section: (1) Silicon Oxide Based Nano-ledmentioning
confidence: 99%
“…Davis et al 11 fabricated a Schottky photodiode having a very small ͑100 nm͒ optically sensitive region on a cantilever, and demonstrated optical imaging with a high resolution similar to the size of the diode aperture. Hoshino et al 12 demonstrated near-field imaging results using a monolithically grown silicon light emitting diode on a scanning probe tip. These probes do improve the SNR of typical NSOM and may be cost competitive with aperture and apertureless NSOM.…”
mentioning
confidence: 98%
“…Since we have proven that the cloak allows field penetration inside the cloak, at levels comparable to the uncloaked scenario, owing to reciprocity it is expected that a source placed inside the cloak may be able to efficiently radiate. In this sense, we have considered an active region at the NSOM tip, which may be obtained by coating the tip with a limited number of quantum dots or emitting molecules, as in a nano-LED for near-field illumination and sensing [4]. We consider an emitting molecule placed on the aperture of the same tip as in Fig.…”
Section: Prl 105 263906 (2010) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 99%
“…In the aperture mode, the tip's opening is used to collect and/ or illuminate the subwavelength detail of objects of interest, whereas in the apertureless operation a very sharp tip is mainly used as a resonant scatterer to enhance and focus light on the subwavelength detail of interest. Recently, apertureless NSOMs have also been used in conjunction with collections of quantum dots localized on the tip to illuminate the detail of interest [4]. Although the apertureless method may ensure a smaller tip size and a larger scattering enhancement for small objects, which results in overall higher resolution, the aperture mode remains more popular, due to its flexibility and simplicity of operation, combined with longer history.…”
mentioning
confidence: 99%